Ventricular Tachycardia Associated Syncope in a Patient of Variant Angina without Chest Pain - Kim, Soo Jin (Korean Circ J, 2016)
A 68-year-old man was admitted for a syncope workup. After routine evaluation, he was diagnosed with syncope of an unknown cause and was discharged from the hospital. He was readmitted due to dizziness. On repeated Holter monitoring, polymorphic ventricular tachycardia was detected during syncope. We performed intracoronary ergonovine provocation test; severe coronary spasm was induced at 70% stenosis of the proximal left anterior descending artery. The patient was treated with percutaneous coronary intervention. We present a rare case of syncope induced by ventricular arrhythmia in a patient with variant angina without chest pain.